Mousterian lithic technology an ecological perspective - Kuhn, Steven L. (Princeton Univ. Press, 1995)
Human beings depend more on technology than any other animal - the use of tools and weapons is vital to the survival of our species. What processes of biocultural evolution led to this unique dependence? Steven Kuhn turns to the Middle Paleolithic (Mousterian) and to artifacts associated with Neandertals, the most recent human predecessors. His study examines the ecological, economic, and strategic factors that shaped the behavior of Mousterian tool makers, revealing how these hominids brought technological knowledge to bear on the basic problems of survival